Workplace fraud and theft in SMEs: evidence from the mobile telephone sector in Nigeria - Yekini, Kemi C.; Ohalehi, P.; Oguchi, I.; Abiola, O. (Emerald, 2017)
Purpose - This study investigates employee fraud within small enterprises in the Nigerian mobile phone sector. It also seeks to understand the key factors that motivate employees to engage in fraudulent behaviours against their employers, and the consequences of these fraudulent behaviours on small businesses (SMEs) in Nigeria.